2014
DOI: 10.5137/1019-5149.jtn.9701-13.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statins on aneurysmal subarachnoid hemorrhage: a meta-analysis of randomized controlled trials

Abstract: AIm:The role of statins for treating aneurysmal subarachnoid hemorrhage (aSAH) remains uncertain. In this study, the relevance of different end points was evaluated in order to clarify the action and efficacy of statins. mAterIAl and methOds: A systematic literature retrieval was carried out to obtain randomized controlled trials (RCTs) from before March 2013 on the use of statins for aSAH. Data extraction and quality evaluation of the studies were performed by 2 investigators. A meta-analysis was performed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
2
11
0
1
Order By: Relevance
“…This finding is contradictory to 5 previous meta-studies and consistent with 2 meta-analyses previously published. 16,17,33,34,36,41,48 The results regarding the secondary outcomes were disappointing. We found no evidence that statin treatment can improve DIND or delayed cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is contradictory to 5 previous meta-studies and consistent with 2 meta-analyses previously published. 16,17,33,34,36,41,48 The results regarding the secondary outcomes were disappointing. We found no evidence that statin treatment can improve DIND or delayed cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…5,10,18,37,42,44 Meta-analyses have also produced inconsistent results. Four studies demonstrated a beneficial effect of statin treatment in at least 1 aspect, 33,34,36,48 while no benefits were reported by the authors of 3 additional studies. 16,17,41 Recently, 2 large-scale multicenter Phase III trials-Simvastatin in Aneurysmal Subarachnoid Hemorrhage (STASH) and High-Dose Simvastatin for Aneurysmal Subarachnoid Hemorrhage (HDS-SAH)-yielded disappointing findings; no benefits of simvastatin treatment were observed in patients with aneurysmal SAH during the STASH study, while authors of the HDS-SAH study reported that treatment with high doses of simvastatin (80 mg) was no more effective than treatment with low doses (40 mg).…”
mentioning
confidence: 91%
“…As in one earlier study the treatment with simvastatin was able to inhibit the development of elastase‐induced pulmonary emphysema in mice (Takahashi et al, 2008), these findings highlight the diversity in the pleiotropic effects within this class of drugs. Differences between statins are also evident from the clinical trials, which are, nevertheless, showing reduced PH and improvement in lung function in COPD–PH patients treated with statins (Lu et al, 2019; Reed et al, 2011; Zhang et al, 2017). It is worth mentioning that even in those patients that benefited from the statin treatment, reduction in PAP was moderate compared with the complete reversal of PH seen in animal models.…”
Section: Pharmacological Therapies For Ph In Animal Models Of Copdmentioning
confidence: 99%
“…It is most severe on the large blood vessels proximally from the ruptured aneurysm. Angiographicaly is proven that the vasospasm is not worsened by surgical manipulation with the vessels [20]. The predictive factors of vasospasm are huge advantage compared to other forms of stroke in terms of therapeutic window for early or preventive treatment.…”
Section: Discussionmentioning
confidence: 99%